Ragam pengakuan formal terhadap penguasaan tanah adat di Indonesia - Guntur, I Gusti Nyoman (Tunas Agraria, 2023)
In fact, in positive law in Indonesia, there is a policy of recognizing customary or ulayat lands from the Customary Law Community (HMA). However, operational arrangements and practices are limited to the recognition of objects and not yet complete in the recognition of subjects and legal relations. Customary or ulayat land is not an object of registration (PP No. 24/1997) but is recorded in the land register (Permen ATR/KBPN No. 18/2019). The inconsistency between the constitution and implementing regulations has the potential to cause differences in the practice of recognition administration. This research with a socio-legal approach was conducted in Central Kalimantan, Banten, West Sumatra, and Bali. The results found that there are regional regulations that recognize customary land ownership with various administrations. First, it does not recognize ownership by MHA because of its certification through the granting of rights to individuals. Second, recognition of objects by administering them on registration maps and land registers without clear status and owners Third, recognition (conversion) by issuing a HM certificate whose subject matter is communal and/or individual (individual or jointly owned). Certification as individual property has transferred ownership from communal to individual ownership. Opportunities for registration that do not change the subject of ownership can be carried out by examining: 1) determining the subject of ownership rights and the subject of user rights; 2) dimensions of the legal relationship of ownership and use; and 3) boundaries of customary land that are not cultivated intensively.   Sesungguhnya dalam hukum positif di Indonesia terdapat kebijakan pengakuan tanah adat/ulayat dari Masyarakat Hukum Adat (HMA). Namun operasional pengaturan dan praktiknya sebatas pengakuan obyek, belum tuntas dalam pengakuan subyek dan hubungan hukum. Tanah adat/ulayat bukan obyek pendaftaran (PP No. 24/1997), namun dicatat dalam daftar tanah (Permen ATR/KBPN No. 18/2019). Ketidakselarasan antara konstitusi dengan peraturan pelaksanaan potensi menimbulkan perbedaan dalam praktik administrasi pengakuan. Penelitian dengan pendekatan sosio-legal ini dilakukan di Kalimantan Tengah, Banten, Sumatera Barat dan Bali. Hasilnya menemukan bahwa terdapat peraturan daerah yang mengakui pemilikan tanah adat dengan beragam penatausahaan. Pertama, tidak mengakui kepemilikan oleh MHA karena sertipikasinya melalui pemberian hak kepada individu. Kedua, pengakuan obyek dengan mengadministrasikan pada peta pendaftaran dan daftar tanah, tanpa ada kejelasan status dan pemilik. Ketiga, pengakuan (konversi) dengan penerbitan sertipikat HM yang subyeknya komunal dan/atau individu (perorangan atau milik bersama). Pensertipikatan menjadi milik individu telah mengalihkan kepemilikan dari komunal menjadi milik individu. Peluang pendaftaran yang tidak merubah subyek kepemilikan dapat dilakukan dengan pencermatan dalam: 1) penentuan subyek hak kepemilikan dan subyek hak pemakai; 2) dimensi hubungan hukum kepemilikan dan pemakaian; dan 3) batas-batas tanah adat yang tidak digarap secara intensif.